Implementation of Legal Fishing Operational Letter (LFOL) in 5 GT-tuna handline fishing boat in Bitung, Indonesia - Lumempouw, Theodoor F.; Budiman, Johnny; Karwur, Denny (Universitas Sam Ratulangi, 2016)
Title (Bahasa Indonesia): Penerapan Surat Laik Operasi (SLO) pada kapal perikanan tuna handline berukuran sampai 5-GT di Bitung, Indonesia This study was carried out in Bitung Oceanic Fishing Port (BOFP) focusing on fishing vessel operations and necessary documents, and tuna production. Data were analyzed using SWOT on legal fishing operation documents of handline tuna fishing boats up to 5-GT. Implementation of legal fishing operation letter (LFOL) started in 2011. Mean catch was 82.565 kg/month under 182 boats/month. This study concluded that the readiness of legal umbrella, supporting facilities, and the human resources for fish resources management in the integrated service center to prevent the IUU Fishing in the Fisheries Management Authority of 715 and 716 were still not optimal. On the other hand, the impact of the legal fishing operation letter implementation on the handline tuna fishing boat up to 5-GT has still not followed Marine and Fisheries Minister’s Regulation No. 45, 2014. Therefore, the study reccommends some revisions of the regulations to optimize the implementation in future. Penelitian ini dilakukan di Pelabuhan Perikanan Samudera Bitung (PPS Bitung) mengenai operasional dan kelengkapan kapal serta produksi ikan tuna. Analisis data menggunakan SWOT terhadap penerapan surat laik operasi (SLO) pada kapal perikanan tuna handline berukuran sampai 5-GT. Penerapan SLO telah dimulai sejak tahun 2011 oleh Dinas Kelautan dan Perikanan (DKP) Kota Bitung. Jumlah rata-rata hasil tangkapan ikan pada perikanan handline tuna adalah sebanyak 82.565 kg/bulan dengan jumlah rata-rata 182 kapal/bulan. Dapat disimpulkan, bahwa kesiapan payung hukum, fasilitas pendukung dan SDM pengawasan/ pengendalian sumber daya ikan yang ada di Pos Pelayanan Terpadu dalam mengantisipasi IUU Fishing di WPP 715 dan WPP 716 masih belum optimal. Pelaksanaan penerbitan SLO bagi kapal perikanan berukuran sampai 5-GT masih berbeda dengan penerapan Permen KP No. 45 Tahun 2014, sehingga perlu dilakukan revisi demi perbaikan produk regulasi dari Kementerian Perikanan Dan Kelautan Indonesia di masa datang.